Diuretics for hypertension - reasons for a contradiction in primary care prescribing behavior: a qualitative study - Lamers, Henrik; Joos, Stefanie; Götz, Katja; Krug, Katja; Szecsenyi, Joachim; Kühlein, Thomas (The journal of clinical hypertension, 2012)
There has been a long international discussion on diuretics as first-line therapy for hypertension. In Germany, thiazide diuretics are very rarely prescribed in monotherapy and concurrently highly prescribed in fixed-combinations. The aim of this study was to approach the reasons for this inconsistency in primary care prescribing behavior. A qualitative study design consisting of single interviews with general practitioners (GPs) was chosen. Most GPs perceived diuretics as too weak to treat arterial hypertension effectively in monotherapy. In combination therapy, GPs expected to spare the dose and to offset certain side effects of other drugs. The convenient availability of diuretics in most fixed-dose combinations on the German drug market was seen as an important reason for their frequent prescription in combination therapy. Thus, the reasons given by the GPs differed from the main arguments of the academic debate. Dissemination strategies for guidelines should take the perceptions and opinions of practicing GPs into account.